RIBBED SMOKE SHEET (RSS) PRODUCT QUALITY CONTROL USING STATISTICAL QUALITY CONTROL (SQC) AT PT. XYZ - Nina Hairiyah; Imron Musthofa; Iis Sakhatun (BPFP Faperta UNIB, 2022)
One of the industries that process latex and lumps into sheets with quality RSS 1, RSS 2, and cutting is PT. XYZ is located in Banjar Regency, South Kalimantan. In the production process, PT. XYZ produces more RSS 2 and cutting products compared to its main product, namely RSS 1. This is due to various factors that result in a decrease in product quality. The purpose of this study is to analyze the quality control of RSS by using statistical quality control (SQC). The tools used are check sheets, Pareto diagrams, P control charts, and cause and effect diagrams. Based on the research that has been done, it is found that a lot of data are outside the control limits of UCL and LCL, which are caused by the initial acceptance of raw materials and the smoking process that is not up to standard. Improvements that need to be made by PT. XYZ is by maintaining the cleanliness of raw materials and placing operators to research on the RSS processing process.